2015
DOI: 10.1016/j.ymben.2015.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative prediction of genome-wide resource allocation in bacteria

Abstract: Predicting resource allocation between cell processes is the primary step towards decoding the evolutionary constraints governing bacterial growth under various conditions. Quantitative prediction at genome-scale remains a computational challenge as current methods are limited by the tractability of the problem or by simplifying hypotheses. Here, we show that the constraint-based modeling method Resource Balance Analysis (RBA), calibrated using genome-wide absolute protein quantification data, accurately predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
198
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(212 citation statements)
references
References 48 publications
5
198
1
Order By: Relevance
“…In this respect, cyanobacterial phototrophic growth is an ideal test case because the regular and periodic environmental changes allow us to formulate the global resource allocation problem in a welldefined way. As yet, similar efforts to investigate proteome allocation have primarily focused on heterotrophic organisms in time-independent environments (21,24,41). These recent analyses reveal several interesting differences with respect to our results.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…In this respect, cyanobacterial phototrophic growth is an ideal test case because the regular and periodic environmental changes allow us to formulate the global resource allocation problem in a welldefined way. As yet, similar efforts to investigate proteome allocation have primarily focused on heterotrophic organisms in time-independent environments (21,24,41). These recent analyses reveal several interesting differences with respect to our results.…”
Section: Discussioncontrasting
confidence: 53%
“…1. In contrast to conventional FBA, and following recent developments in constraint-based analysis (18,(23)(24)(25)(26), the capacity constraints of individual reactions are explicitly part of the model.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evolutionary theories suggest that protein expression levels maximize fitness (Dekel & Alon, 2005;Molenaar et al, 2009;. In particular, the growth rate-dependent regulations may contribute to cost minimization by providing reasonable solutions to the cost-benefit optimization of the cellular and metabolic processes that must be active under all growth conditions and consequently to fitness increase across growth conditions (Goelzer et al, 2015). We revealed that the variations in the free ribosome abundance can globally contribute to proper cellular (re)programming and have evidenced a unique, hard-coded, growth rate-dependent mode of translation regulation, which manages genome-wide gene expression in addition to specific post-transcriptional and translational regulations.…”
Section: Translation Efficiency Based On Michaelis-menten Kinetics: Tmentioning
confidence: 99%
“…The approach we present here characterizes the quantitative relationship between enzymatic catalysis in vitro and in vivo and offers a highthroughput method for extracting enzyme kinetic constants from omics data. (1)(2)(3)(4)(5)(6). Many models of cellular metabolism include k cat values, the maximal turnover rates of enzymes, as key inputs to predict the behavior of metabolic pathways and networks (7)(8)(9).…”
mentioning
confidence: 99%